RBE study using solid state microdosimetry in heavy ion therapy. (November 2017) - Bolst, David; Tran, Linh T.; Chartier, Lachlan; Prokopovich, Dale A.; Pogossov, Alex; Guatelli, Susanna; Reinhard, Mark I.; Petasecca, Marco; Lerch, Michael L.F.; Matsufuji, Naruhiro; Perevertaylo, Vladimir L.; Fleta, Celeste; et al.
Abstract: The response of two types of 10 μm thick silicon-on-insulator (SOI) detectors in a 12 C ion therapy beam with extremely high spatial resolution are presented in this work. The two detectors used are the "bridge" microdosimeter with isolated 3D sensitive volumes (SVs) and the ultra-thin 3D (U3DTHIN) detector with n + and p + 3D columnar structures. Both detectors were investigated at various depths in a water phantom along the central axis of the spread-out Brag peak (SOBP) of a 290 MeV/u 12 C ion beam at the Heavy Ion Medical Accelerator in Chiba, Japan. Based on the Microdosimetric Kinetic (MK) model and the microdosimetric quantities measured with the two detectors, the relative biological effectiveness (RBE) values were derived and compared to results obtained with the tissue-equivalent proportional counter (TEPC). Derived RBE10 values obtained with the U3DTHIN detector were considerably higher than those obtained with the bridge microdosimeter and the TEPC along the SOBP. Due to the high spatial resolution of the microdosimeters, more detailed measurements were obtained at the end of the SOBP compared to the TEPC. The maximum derived RBE10 found using the U3DTHIN detector and bridge microdosimeter were approximately 2.66 and 2.58, respectively which are higher than the RBE10 value of 2.35 obtained with the TEPC due to the lack of high spatial resolution in the TEPC. The discrepancy in the results obtained using the two detectors is due to the difference in geometry of the SVs in the two detectors. This work presents an application of different types of SOI micodosimeters in a 12 C ion therapy beam and has demonstrated that the microdosimeter with micron sized 3D SVs is more desirable for accurate lineal energy measurement and RBE determination. Silicon microdosimetry has demonstrated a simple, fast and accurate method for routine Quality Assurance in charged particle therapy. Highlights: The application of the silicon microdosimeters for RBE determination in heavy ion therapy was presented. Effect of chord length in various sensitive volume shapes was investigated. Comparison of RBE and biological dose in heavy ion therapy obtained with two different silicon microdosimeters was presented.